2012
DOI: 10.1016/j.jaap.2012.04.007
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study on the pyrolysis of metal- and ash-enriched wood and the combustion properties of the gained char

Abstract: This study aims to investigate the pyrolysis behaviour of metal-contaminated wood and the combustion properties of char derived from wood pyrolysis. Seven metals (Na, Mg, Ca, Zn, Cd, Pb and Fe(III)) were introduced to willow in cation form by ion-exchange and the thermal behaviour of demineralised samples and samples with additional ash were also investigated. The results show that the char yield increased from 21% to 24-28% and levoglucosan yield in vapour phase decreased from 88% to 62-29% after the addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(43 citation statements)
references
References 47 publications
1
42
0
Order By: Relevance
“…The smaller activation energy in the early stage of the thermal decomposition of cellulose has been observed in the presence of natural inorganic salts (Nam et al 2014). Various metal ions introduced by ion exchange have been shown to affect the thermal behavior of cellulose (Mayer et al 2012;Richards and Zheng 1991;Soares et al 1998). The dominant role of sodium in cellulose combustion was demonstrated by the variations in HRC and char yield with the concentration of Na, K, and P, as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The smaller activation energy in the early stage of the thermal decomposition of cellulose has been observed in the presence of natural inorganic salts (Nam et al 2014). Various metal ions introduced by ion exchange have been shown to affect the thermal behavior of cellulose (Mayer et al 2012;Richards and Zheng 1991;Soares et al 1998). The dominant role of sodium in cellulose combustion was demonstrated by the variations in HRC and char yield with the concentration of Na, K, and P, as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Earlier studies (Mayer et al 2012;Richards and Zheng 1991) reported that inorganic compounds introduced to wood cellulose by ion exchange influenced its pyrolysis and combustion, depending on the types and concentration of metals present. This study showed that sodium plays an important role in lowering the thermal decomposition temperature of cellulose, which resulted in reduced oxygen consumption for combustion and increased char yield.…”
Section: Resultsmentioning
confidence: 99%
“…It showed a stable mass loss rate for the used RHC Ni from 400 to 500°C, possibly ascribed to the fixed carbon burn off. Basically, the burnout temperature of char and coke (R9) was over 500°C [44], where the mass loss rate of the used 10 g-RHC Ni decreased, compared to the used 3 g-RHC Ni and 5 g-RHC Ni. It is also indicated that hydrocarbons decomposition (R10) and carbon deposition (R11) are easier take place when a small amount of catalyst is employed.…”
Section: Tg Analysismentioning
confidence: 99%
“…It is worth noting that the barley straw pellets contain nearly twice as much ash as wood pellets (6 wt.% for barley straw compared with 3.6 wt.% for wood). Ash in the feedstock can seriously affect the yield and characteristics of char, and is considered undesirable in the feedstock (Mayer et al 2012). …”
Section: Feedstockmentioning
confidence: 99%